2020
DOI: 10.1371/journal.pone.0243008
|View full text |Cite
|
Sign up to set email alerts
|

Association between Trypanosoma cruzi DTU TcII and chronic Chagas disease clinical presentation and outcome in an urban cohort in Brazil

Abstract: Background The specific roles of parasite characteristics and immunological factors of the host in Chagas disease progression and prognosis are still under debate. Trypanosoma cruzi genotype may be an important determinant of the clinical chronic Chagas disease form and prognosis. This study aimed to identify the potential association between T. cruzi genotypes and the clinical presentations of chronic Chagas disease. Methodology/principal findings This is a retrospective study using T. cruzi isolated from b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…It was not possible to differentiate the subgroups TcV from TcVI. The patients who have the samples genotyped were from the Southeastern Brazil (states of São Paulo and Minas Gerais), confirming the prevalence of subtype TcII [ 18 , 23 ]. These patients present the clinical forms undetermined, cardiac or mixed (i.e.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…It was not possible to differentiate the subgroups TcV from TcVI. The patients who have the samples genotyped were from the Southeastern Brazil (states of São Paulo and Minas Gerais), confirming the prevalence of subtype TcII [ 18 , 23 ]. These patients present the clinical forms undetermined, cardiac or mixed (i.e.…”
Section: Discussionmentioning
confidence: 74%
“…In reports from the literature, blood culture for T . cruzi presented sensitivity ranging 38%–53% in patients with Chagas disease [ 18 , 19 ]. In this study, the blood culture positivity was 44% (8/18), being within the range reported by other authors.…”
Section: Discussionmentioning
confidence: 99%
“… 7 This variability has been associated with factors related to both host and parasite. 8 One possible explanation may be derived from parasites’ genetic background. These parasites show a high genetic variability being assembled into seven distinct genetic groups, or discrete typing units (DTU): TcI-VI and TcBat.…”
mentioning
confidence: 99%
“… 9 All of them can infect humans and their frequency varies depending on the geographic location. 8 , 9 The link between T. cruzi genotype and the clinical manifestations (or drug susceptibility) of Chagas disease has been proposed but has not been proved yet. 6 , 7 , 9 So far, there is no vaccine available and only two drugs, benznidazole ( 1 ) and nifurtimox ( 2 ), are clinically used.…”
mentioning
confidence: 99%
“…Another relevant aspect of this discussion is the fact that only through prospective studies, where long-term follow-up of individuals is carried out, it is possible to correlate the findings with the clinical forms of the disease 5 , 6 . Cross-sectional studies do not allow us to infer cause-effect relationships, but plausible hypotheses may be raised.…”
mentioning
confidence: 99%